Enhanced electro-oxidation resistance of carbon electrodes induced by phosphorus surface groups. (December 2015) - Berenguer, R.; Ruiz-Rosas, R.; Gallardo, A.; Cazorla-Amorós, D.; Morallón, E.; Nishihara, H.; Kyotani, T.; Rodríguez-Mirasol, J.; Cordero, T.
Abstract: The electro-oxidation of carbon materials enormously degrades their performance and limits their wider utilization in multiple electrochemical applications. In this work, the positive influence of phosphorus functionalities on the overall electrochemical stability of carbon materials has been demonstrated under different conditions. We show that the extent and selectivity of electroxidation in P-containing carbons are completely different to those observed in conventional carbons without P. The electro-oxidation of P-containing carbons involves the active participation of phosphorus surface groups, which are gradually transformed at high potentials from less-to more-oxidized species to slow down the introduction of oxygen groups on the carbon surface (oxidation) and the subsequent generation of (C*OOH)-like unstable promoters of electro-gasification. The highest-oxidized P groups (–C–O–P-like species) seem to distribute the gained oxygen to neighboring carbon sites, which finally suffer oxidation and/or gasification. So it is thought that P-groups could act as mediators of carbon oxidation although including various steps and intermediates compared to electroxidation in P-free materials.